2006
DOI: 10.1109/tit.2006.883609
|View full text |Cite
|
Sign up to set email alerts
|

Universal Lossless Compression With Unknown Alphabets—The Average Case

Abstract: Universal compression of patterns of sequences generated by independently identically distributed (i.i.d.) sources with unknown, possibly large, alphabets is investigated. A pattern is a sequence of indices that contains all consecutive indices in increasing order of first occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(58 citation statements)
references
References 37 publications
(174 reference statements)
1
57
0
Order By: Relevance
“…Gil Shamir [18] suggests that a bound of similar order can be obtained by properly updating (B12) in [11]. The proof provided in this paper was elaborated independently; both of them use the channel capacity inequality described in Section 3..…”
Section: Theorem 1 For All Integers N Large Enough the Maximin Pattementioning
confidence: 99%
See 3 more Smart Citations
“…Gil Shamir [18] suggests that a bound of similar order can be obtained by properly updating (B12) in [11]. The proof provided in this paper was elaborated independently; both of them use the channel capacity inequality described in Section 3..…”
Section: Theorem 1 For All Integers N Large Enough the Maximin Pattementioning
confidence: 99%
“…It was first introduced byÅberg in [8] as a solution to the multi-alphabet coding problem, where the message x contains only a small subset of the known alphabet A. It was further studied and motivated in a series of articles by Shamir [9][10][11][12] and by Jevtić, Orlitsky, Santhanam and Zhang [13][14][15][16] for practical applications: the alphabet is unknown and has to be transmitted separately anyway (for instance, transmission of a text in an unknown language), or the alphabet is very large in comparison to the message (consider the case of images with k = 2 24 colors, or texts when taking words as the alphabet units).…”
Section: Dictionary and Patternmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial work on patterns [5], [7], [11], [15], [16], focused on showing diminishing universal compression redundancy rates. The first results on pattern entropy in [11], [14], [16], however, showed that for sufficiently large alphabets, the pattern block entropy must decrease from the i.i.d.…”
mentioning
confidence: 99%